The Integration of Pancasila Values in Building Students’ Character as An Effort to Prevent Lost Generation At SMP Muhammadiyah 1 Makassar - Jumiati Nur; Musdalifah Syahrir; Dewa Bagus Sanjaya; Ya’kub Ya’kub; Sharah Adriani Jafar (Universitas of Muhammadiyah Makassar, 2023)
This study aims to describe the integration of Pancasila values in building the character of students as an effort to prevent the Lost Generation and the inhibiting factors in integrating Pancasila values in the school environment of SMP Muhammadiyah 1 Makassar. This study uses a descriptive qualitative method. Data collection techniques include observation, interviews, and documentation. Research findings: 1. The integration of Pancasila values is carried out through various main activities at the school, namely: (1) through moral habituation or moral culture within the school, (2) during the Civics Education (PPKn) learning process, and (3) through extracurricular activities conducted at the school. 2. Inhibiting factors in integrating Pancasila values at the school include both internal and external factors. Internal factors are caused by inadequate funding and resources from the school, while external factors involve a lack of support from students' parents and the social environment.